2002
DOI: 10.1046/j.1365-2036.2002.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of irritable bowel syndrome

Abstract: SUMMARY The efforts of clinical researchers, lay organizations and pharmaceutical companies have increased the public profile of irritable bowel syndrome and made it a respectable diagnosis. Diagnostic symptom criteria encourage a firm clinical diagnosis, which is the foundation of a logical management strategy. This begins with education. Reassurance that no structural disease threatens should be tempered with the reality that symptoms are likely to recur over many years. Patients expect diet and lifestyle ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 84 publications
1
20
0
1
Order By: Relevance
“…All patients entered into the study met the Rome II criteria for IBS: 12 consecutive or non-consecutive weeks or more in the past 12 months of abdominal discomfort or pain with two of the three features of (1) relief with defecation, (2) onset associated with a change in stool frequency and/or (3) onset associated with a change in the form (appearance) of the stool 24 36 37…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients entered into the study met the Rome II criteria for IBS: 12 consecutive or non-consecutive weeks or more in the past 12 months of abdominal discomfort or pain with two of the three features of (1) relief with defecation, (2) onset associated with a change in stool frequency and/or (3) onset associated with a change in the form (appearance) of the stool 24 36 37…”
Section: Methodsmentioning
confidence: 99%
“…Other possible therapies have included clonidine,19 cholestyramine,18 Chinese herbal therapy,20 21 cromolyn22 23 and psychotherapy 24 25. Antispasmodic agents such as hyoscyamine and dicyclomine are often prescribed but have not been established to be beneficial and may lose any possible benefit over time 7.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive gastrointestinal symptom profile was obtained when patients completed the Rome II integrative questionnaire at the time of the screening interview. Women were eligible to participate if they met Rome II criteria for IBS and had been diagnosed by a gastroenterologist within a year prior to the study [16,17]. In the event that a potential participant had not been diagnosed within the past year, a gastroenterologist at the Thomas N. Lynn Institute for Healthcare Research confirmed the diagnosis of IBS.…”
Section: Recruitment and Screening Of Participantsmentioning
confidence: 99%
“…22 PDS is een chronische aandoening, waarbij 88% van de patiënten na 8 jaar followup nog steeds symptomen vertoont. 23 Bij slechts een klein aantal van de in de huisartsenpraktijk gediagnosticeerde patiënten wordt een organische verklaring gevonden. Tot nu toe zijn routineonderzoeken naar colorectaal carcinoom, coeliakie of andere mogelijke organische diagnoses niet kosteneffectief gebleken.…”
Section: Samenvattingunclassified